2017
DOI: 10.1002/gps.4794
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex‐related differences in risk factors for elderly suicide: Differentiating between suicide ideation and attempts

Abstract: This study revealed that factors known to influence suicide ideation in the elderly from previous studies, such as residence area, separation from a spouse, education level, religion, and drinking, show changed influence as the elderly reach their 70s and 80s. However, a negative perception of one's own health status was a risk factor that encompassed most ages and sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
4
19
0
1
Order By: Relevance
“…Studies included in this article showed different lifestyle behaviors in different lifestages. In adolescent and young adults there are multiple important risk factors for suicide including psychosis, depression, low sleep satisfaction, high stress, substance abuse, alcohol consumption, smoking, sexual activity, internet addiction, interpersonal factors, personality disorders, anxiety or conduct disorders, eating disorders, and aggressive, irritable and antisocial tendencies ( 38 , 39 ). Though it has been demonstrated that school-based suicide prevention programs increase knowledge on suicide without really preventing suicidal behaviors ( 133 ), it seems necessary to consider prevention programs that identify substance abuse, educational competencies (literacy, study skills, time management), educational environment, school programs, social interactions, academic attainment, cognitive progress, emotional control, behavioral expectations, physical and moral development, and encouragement of active engagement in sports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies included in this article showed different lifestyle behaviors in different lifestages. In adolescent and young adults there are multiple important risk factors for suicide including psychosis, depression, low sleep satisfaction, high stress, substance abuse, alcohol consumption, smoking, sexual activity, internet addiction, interpersonal factors, personality disorders, anxiety or conduct disorders, eating disorders, and aggressive, irritable and antisocial tendencies ( 38 , 39 ). Though it has been demonstrated that school-based suicide prevention programs increase knowledge on suicide without really preventing suicidal behaviors ( 133 ), it seems necessary to consider prevention programs that identify substance abuse, educational competencies (literacy, study skills, time management), educational environment, school programs, social interactions, academic attainment, cognitive progress, emotional control, behavioral expectations, physical and moral development, and encouragement of active engagement in sports.…”
Section: Discussionmentioning
confidence: 99%
“…Im et al ( 38 ) examined 370,568 students with the aim of recognizing risk factors for suicidal ideation in adolescents found that low sleep satisfaction, high stress, alcohol consumption, smoking, and sexual activity, were significant lifestyle factors associated with suicidal ideation. Lee et al ( 39 ) in a sample of 860 adolescents confirmed the relationship between several lifestyle behaviors and suicide risk including sleep disturbance, internet game addiction, and interpersonal factors (e.g., family conflicts and peer problems). A recent systematic review of 17 studies recognized that, in adolescents, a diagnosis of binge eating disorder was predictive of suicidality, while a high body mass index (BMI) was not ( 40 ).…”
Section: Lifestyle Behavior and Suicide In Adolescents And Young Peopmentioning
confidence: 91%
See 1 more Smart Citation
“…[30][31][32] In terms of the mediating factors between these demographic or physical health-related variables, stress cognition, and depressive mood have been identified as some of the most influential factors in SI. Previous researches have reported that various demographic risk factors increase suicidality, including older age, 33 being an unmarried male, 34 and having lower economic status. 35 In a meta-analysis, alcohol abuse was also reported as a significant risk factor for SI [odds ratio (OR)= 1.86] as well as for suicide attempts and completed suicide.…”
Section: Depressive Mood: a Risk Factor And Possible Mediator Betweenmentioning
confidence: 99%
“…Although many suicide risk factors have been identified, it is difficult to predict the real reason for the high suicide rate in older adults . Previous studies have reported that ill health, loss of function due to aging, terminal illness, chronic pain, mental health problems—such as depression, social isolation, a lack of support systems—and financial difficulties were risk factors for death by suicide in older adults .…”
Section: Introductionmentioning
confidence: 99%